Anxiety and Depression Comorbidities in Moroccan Patients With Breast Cancer - El kherchi, Ouassil; Aquil, Amina; El khoudri, Noureddine; Mouallif, Mustapha; Daghi, Mohamed; Guerroumi, Maroua; Saad, El madani; Benider, Abdellatif; Jayakumar, Arumugam R.; Elgot, Abdeljalil (Frontiers in Psychiatry, 2021)
Background: Breast cancer is the leading cause of cancer death in women worldwide with more than 1.7 million new cases annually. Major advances have been made in the therapeutic management of this condition in many countries. However, neuropsychiatric disorders in patients with breast cancer constitute a significant concern due to their negative impact on patient’s life and on the success of therapy itself. Methodology: In this study we aimed to evaluate psychological disorders in a population of 212 Moroccan women treated for breast cancer within the Mohammed VI Center for the Treatment of Cancers of Casablanca. A questionnaire was designed to this end on the basis of different validated scales including the Hospital Anxiety Depression Scale (HADS), the Pittsburgh Sleep Quality Index (PSQI) and the Body Image Scale (BIS). Results: Data analysis have shown that 69.3% of participants had significant sleep disorders; 87% suffer from an anxiety-depressive syndrome (ADS), and 83.0% had significant body image dissatisfaction. A positive correlation was shown between ADS and both patients’ national health insurance coverage and patients or husbands’ education. Analysis further revealed that anxiety and depression were negatively correlated with different types of treatment. Similarly, the BIS and PSQI findings were associated with both anxiety and depression. Conclusion: The present investigation highlights the need to generalize and strengthen the psychological approach of patients treated for breast cancer in Morocco. Such strategy we anticipate will alleviate suffering and promote therapy success in these patients which will diminish or prevent conjugal and familial impacts of the illness.